Aplikasi Arang Sekam terhadap Pertumbuhan dan Produksi Rumput Benggala (Panicum maximum). - Richardus Fretis; Stefanus Sio; Theresia I. Purwantiningsih (JAS, 2022)
This study aimed to determine husk charcoal's effect on the growth and production of Bengal Grass (Panicum maximum). The method used in this study is an experimental method using a completely randomized design (CRD) with 4 treatments and 3 replications. The variables measured in this study included plant height, number of leaves, fresh weight, and dry weight. The treatments were A0 (without husk charcoal), A1 (150 gr husk charcoal), A2 (200 gr husk charcoal), and A3 (250 gr husk charcoal). The results showed that the highest average growth was in the cultivation of A2 plants = 61,15 cm (plant height); A2 = 58,22 pieces (number of leaves); A2 = 779,88 g (fresh weight); and A3 = 505,60 g (dry weight). It concluded that all treatments applied with different doses of husk charcoal gave the best results in treatment A2 (husk charcoal 200 g) on the variables of plant height, number of leaves, and plant fresh weight, while on the variable dry weight of plants increased in treatment A3 (husk charcoal 250 g).